Answer:
p=7x
Step-by-step explanation:
49x^[2] + 28x - 10 = p^[2] + 4p -10
This equation is in the form a^[2]x + bx + c.
<u><em>The 'c' is common for both equations, this means the 'a' and 'b' must also be common. </em></u>
There are two ways to find p: 'a' or 'b'
<u>a method</u>
49x^[2] = p^[2]
=> The square root of both sides = 7x = p
<u>b method</u>
28x = 4p
28x/4 = 4p/4
7x = p
Answer:
you use disputation
Step-by-step explanation:
4 times 3x = 12x
4 times 6 = 24
B,C and D are correct because all of those choices include letters which are arranged in order from left of right.